Avaliação da toxicidade aguda e subcrônica e ação antitumoral do extrato hidroalcoólico bruto das folhas de rollinia leptopetala - Lima, Carolina Uchôa Guerra Barbosa de (2013)
The cancer is a disease of the genetic material of our cells and the experimental cancerology has a huge value for the studies of several aspects related to the neoplastic processes. Many drugs used nowadays in chemotherapy were extracted from plants or derived from a natural prototype. However, medicinal plants have aggressive substances and, so, their toxicity must be evaluated. Rollinia leptopetala R.E. Fries, popularly known as angry pine , is a tree or bush endemic in Brasil and is utilized by popular medicine as digestive and against tumors and inflammations. It s barely addressed in the literature, both from the point of view of phytochemist studies as their biological activities. Because of this, this work has the objective of evaluate the antitumor activity and the toxicity of the Brute Hydroalcoholic Extract (BHYE) of the leaves from R. leptopetala, through the assays in vitro and in vivo. The value of CI50 obtained from the assays of the exclusion of the trypan blue was 512,3 μg/mL. Already in the bioassay with A. salina the value obtained from CL50 was 78,49 μg/mL. The BHYE of the leaves from R. leptopetala didn t show significant hemolytic activity in erythrocytes in mice, producing only 10 % of hemolysis in concentrations above 1250 g/mL. In the evaluation of antitumor activity in vivo in sarcoma 180 the rates of inhibition of tumor growth were 8.05, 38.72 and 49.73% after treatment with 50, 100 and 150 mg/kg of the extract, respectively. The toxicological analysis of the animals showed that there was no change in the index of spleen and thymus after the treatments, these alterations that occur with chemotherapy drugs used in clinical practice, nor the kidneys, liver and heart. In the study of the subchronic toxicity, it was observed that the continuous use of the extract at a dose of 90mg/kg, possibly has a diuretic action, which can cause megaloblastic anemia and can affect the Central Nervous System, in addition to increasing the quantity of platelets. Therefore, it is possible to infer that the BHYE from the leaves of R. leptopetala has antitumor activity, but that its continuous usage can cause toxicological damage.